2006
DOI: 10.3844/ajassp.2006.2151.2159
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Quality of Work Life (QWL) and Career- Related Variables

Abstract: Abstract:The aim of this study was to determine the level and relationship between qualities of work life (QWL) with career-related variables. The sample consists of 475 executives from the electrical and electronics industry in the free trade zones in Malaysia for both the multinational corporations (MNCs) and the small-medium industries (SMIs). The selection of respondents using stratified random sampling technique involves a complete list of industrial firms registered with Malaysian Industrial Development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…First, the effectiveness of career development will be obtained if the career development activities carried out jointly between the workers, employers and organizations. Workers, who have a positive perception of career development and supported by the organization, tend to have high motivation to achieve the goals (Rose et al, 2006). Thus, workers who are satisfied with the job and his career will be loyal to the organization and work to improve profitability and productivity of the organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the effectiveness of career development will be obtained if the career development activities carried out jointly between the workers, employers and organizations. Workers, who have a positive perception of career development and supported by the organization, tend to have high motivation to achieve the goals (Rose et al, 2006). Thus, workers who are satisfied with the job and his career will be loyal to the organization and work to improve profitability and productivity of the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Attitude of employees will increase and so will make employees more committed to the organization (Fuller, Barnett, Hetse, & Relyea, 2003). Study conducted by Rose, Beh, Uli, and Idris (2006) found that career satisfaction; career achievement and career balance was significantly correlated with the quality of work life. Workers get training and development opportunities by allowing them to improve their skills and be able to express attitudes and roles in the organization.…”
Section: Career Development and Quality Of Work Lifementioning
confidence: 99%
“…Independentemente das divergências existentes no que respeita à sua conceptualização parece haver um certo consenso relativamente ao facto de ser um constructo amplo e subjetivo, que lida com o bem-estar do indivíduo em relação ao seu trabalho (Pereira, Teixeira, & Santos, 2012). Que inclui de forma complexa a saúde física da pessoa e as tarefas que esta desempenha, o ambiente físico e social em que se insere, o estado psicológico, o nível de independência, as relações sociais, as crenças e convicções pessoais e a relação com os aspetos importantes do meio ambiente (Pinto, Macedo, & Dias, 2013;Roan & Diamond, 2003;Rose, Beh, Uli, & Idris, 2006).…”
Section: Vulnerabilidade Ao Stresse Em Cuidadores Formaisunclassified
“…The concept of quality of work life (QWL) was first discussed in the late 1960s (2). This range of theoretical concepts aimed at modifying the organizational problems.…”
Section: Introductionmentioning
confidence: 99%